A Nine Point Management programme for Clay soils in Uttar Pradesh - singh, S.D. (Journal of Soil and Water Conservation, 2022)
Agricultural land is of value only because of its ability to grow crops. But impeded drainage, lack of aeration, slower and sluggish microbial activities, restricted root ramification, limited right-time-range for ploughing, root injury by cracks as the soil dries, need for heavy resources are the problems of clay-land farming that affect this ability. Remedying these troubles is not an easy task. However, some management practices of agricultural importance may be mentioned to be of some benefit to the clay-land farmers. They can modify these practices as their immediate circumstances permit.